Management of Sacrococcygeal Teratoma in Infants and Children (Medical Forum Monthly, 2023)
ABSTRACTObjective: To discuss the management of SCT in infants and older patients with special attention to per operative, post operative complications like tumor rupture, GIT trauma, neurological function and recurrence.Study Design: A retrospective descriptivePlace and Duration of Study: This study was conducted at the pediatric and neonatal surgery Bahawal Victoria Hospital from March 2017 to March 2022.Materials and Methods: Patients under 2 months and older children (2mnths to 5 year) with SCT were included in the study. All patients were assessed for any associated anomalies. Tumour excision was done either through sacral route only or abdominosacral approach depending upon size and type of SCT. Patients were observed for any perioperative and postoperative complications and then later on follow-up for 30 months.Results: Twenty-five patients with SCT were managed.20 patients under 2 month of age and 5 above 2months upto 5 years of age. Sacral approach (22 patients) was used in small size tumor and abdominosacral approach (3 patients). on histopathology 18 benign and 7 malignant. Patients with Sacral approach all good with fecal and urinary continence whereas sacro abdominal approach showed some form of incontinence. Survival good after chemotherapy.Conclusion: SCT has a good prognosis if operated early with increased rate of complication and malignancy as age of patient and type of tumor increases.